Should the federal government reallocate funds within federal transfers? - Sequeira, T. N.; Ferreira-Lopes, A. (Public Finance Review, 2009)
It is recognized that one of the goals of federal transfers is to provide the states with some financial leverage during recessions. Federal transfers in the United States comprise such components as retirement and disability payments for individuals, other direct payments for individuals or organizations, grants, procurement contracts, and salaries and wages. Is the composition of the federal transfers’ budget having an optimal effect on the business cycle or should the federal government reallocate some expenditure? In this article, we argue that the federal government may improve its role in stabilizing the business cycle if some reallocation is made from procurement contracts and payments for other than individuals to direct payments for individuals, grants, and disability and retirement payments.